The Portuguese TV news coverage of the European Parliament elections 2019 - Bonacho, Fernanda (2021)
The 2019 elections to the European Parliament (EP) were held in a climate of political unrest. The overriding forces of populism and Euroscepticism (blatantly exemplified by Brexit) loomed on the horizon seemingly threatening the process of European integration and the balance of pro- and anti European forces within the EP. Despite the impact and legislative importance of the EU governance upon our lives, a significant body of research has argued that so far there has not been a committed European news agenda focused on fostering citizen engagement with EU affairs so as to build a sense of Europeanness or a Europeanized discursive public sphere. The 2019 elections to the European Parliament (EP) were held in a climate of political unrest. The overriding forces of populism and Euroscepticism (blatantly exemplified by Brexit) loomed on the horizon seemingly threatening the process of European integration and the balance of pro- and anti-European forces within the EP. Despite the impact and legislative importance of the EU governance upon our lives, a significant body of research has argued that so far there has not been a committed European news agenda focused on fostering citizen engagement with EU affairs so as to build a sense of Europeanness or a Europeanized discursive public sphere. The primary goal of this paper is therefore to evaluate the role of the Portuguese television in informing the public and contextualizing the issues posed by the run-up to the EP election and the underlying process of the European construction. In Portugal, television remains a privileged medium for citizens to access information. As stated by OberCom's 2018 report, RTP1 is considered to be the most reliable source of information. Given that prime-time TV news bulletins manage to reach the highest audience ratings, when compared to other information programmes, it is our aim to analyze RTP1, SIC and TVI news bulletins between 13-26 May – the period of the electoral campaign. A critical discourse analysis (combining quantitative and qualitative methods) will be followed in order assess the newsworthiness of Europe -where is Europe? - and the interconnectedness between systems of representation, identity building and participatory citizenship.